Meningkatkan Kompetensi Komunikasi pada Guru dan Siswa dalam Kegiatan Belajar Mengajar (Neolectura, 2022)
Communication is a process of sending messages between two or more people. Messages conveyed can be in the form of oral communication, written communication, verbal communication, non-verbal communication. Effective communication in learning is a process of transforming messages in the form of science and technology from educators to students, where students are able to understand the meaning of messages in accordance with predetermined goals, thereby increasing knowledge and insight into science and technology and causing behavioral changes for the better. In educational communication, an educator must have good personal communication because this will affect to create a harmonious relationship between educators and students. An educator must also have an important role to be able to control healthy classroom conditions because it is a measure of success. The results of this activity indicate that mastering and developing several communication strategies and techniques will automatically increase the ability to relate to various kinds of people. An educator can create and develop effective communication through learning materials that are acceptable and easily understood by students. By increasing the communication competence of teachers and students, teaching and learning activities can run well, effectively and efficiently.